PERSEPSI MAHASISWA TENTANG BANK SYARIAH TERHADAP KEPUTUSAN MENABUNG DI PERBANKAN SYARIAH - Wella Sandria (Universitas Muhammadiyah Jambi, 2018)
Islamic Bank is a bank whose operating system uses sharia principles. Currently many terms are given to refer to Islamic Bank entities other than Islamic Banks themselves, namely Banks Without Riba (La Riba Bank), and Islamic Banks (Shari'a Bank) or banks based on sharia principles. Students are the right target for Islamic banking to increase savings growth. Savings are needed in students, not only students who come from within the city but also come from outside. The purpose of this study is to find out how the Economic School of Muhammadiyah Jambi students’ 'perceptions about Islamic banking, and how strong the influence of students' perceptions on the decision to save in Islamic banks. The theoryies used are perception theory by Michael W. Levine & Shefner and the factors that influence consumer decisions by Mowen and Michael. The results of this study indicate that the perception of students of the Economic School of Muhammadiyah Jambi regarding sharia banking services in Jambi is very positive, indicated by the level of their understanding of Islamic banking services. They believe well that saving in Islamic banks is more beneficial than in conventional banks. However, the decision to save is still in conventional banks. There are only 24.6% of students who have savings in Islamic banks. The remaining 75.4% do not have savings in Islamic banks.